Video game art : game development essentials. - Gantzler, Todd, ....- (New York : Thomson Delmar Learning, 2005)
The premiere title in the Game Development Essentials series explores the art of bringing a game designer's concepts to life. A strong foundation in game artistry is the essential first step, and leading game art designer Todd Gantzler takes readers behind the scenes to show them how to create the entire visual world-from characters to environments-that a game player encounters on the computer screen. Hands-on tutorial instruction suitable for beginning-to-intermediate-level game artists explains the process involved in creating art for real-time 3D digital games and, specifically, video games. The book highlights the technical aspects of preparing art quickly and effectively while conforming to the limitations and specifications of today's most widely used 3D game engines.